"Full body intersection": Fat-Positive Activism, Poetry Slam, and Rachel Wiley. Issue 1 (2nd January 2019) - Schoppelrei, Elizabeth
ABSTRACT: In her poetry and slam poetry, Rachel Wiley draws attention to her various intersecting identities as a "Feminist, Queer, Fat, Mixed Femme Girl" and, through her words, presents societal critiques and imagines better futures. She calls herself a "full body intersection." The flexibility within this term provides a tool to think in relation to intersectionality (and its interlocking systems of oppression) but to also think through the ways in which Wiley's body of work consistently interacts with cultural forces, critiques of poetics, and the physicality of performing on a stage with an ever-watching audience. Moreover, her work elucidates how a full body intersection involves not just the materiality and physicality of the body, it also remains intertwined with visibility, the readings of others, and larger systems of categorical policing. I argue that Rachel Wiley's poetry, in particular a pointed poem such as "For Nicholas Who Is So Concerned, " presents an opportunity for counterhegemonic struggle through fat positivity via considerations of hyper(in)visibility and an articulation of marginalized existence. In illuminating hidden or overlooked systems of oppression and transforming this discrimination into a pressing issue of concern within the larger community, Wiley's work is the force we need in creating counter-hegemonic stories and dismantling oppressive structures.